KONTRIBUSI ANTARA KECEPATAN, KELINCAHAN DAN KOORDINASI MATA-KAKI DENGAN KEMAMPUAN MENGGIRING BOLA DALAM PERMAINAN SEPAK BOLA PADA SISWA MTS NEGERI 1 KOTABARU - M. Imran Hasanuddin; Hasruddin Hasruddin (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2018)
ABSTRACT This research is a kind of quantitative descriptive research. This study aims to determine: (1) To determine whether there is a contribution between the speed with the ability to dribble in the game of football in students of MTs Negeri 1 Kotabaru. (2) To find out whether there is contribution between agility with dribbling ability in game of soccer at student of Â MTs Negeri 1 Kotabaru. (3) To find out whether there is contribution between eye-foot coordination with the ability to dribble in soccer game at students of MTs Negeri 1 Kotabaru. (4) To find out whether there is a contribution between speed, agility and foot coordination with the ability to dribble in a soccer game on students of MTs Negeri 1 Kotabaru. The population is a student of MTs Negeri 1 Kotabaru. The sample used is MTs Negeri 1 Kotabaru students as many as 30 people. The technique of determining the sample is by random selection by drawing method (Simple Random Sampling). Data analysis technique used inferential descriptive analysis analysis through SPSS 20 program at significant level Î± 0,05. The results showed that; (1) there is a significant contribution between the speed with the ability of dribbling in the game of football at the students ofMTs Negeri 1 Kotabaru, amounted to 33.1%, (2) there is a significant contribution between agility with the ability to dribble in the game of football in students MTs Negeri 1 Kotabaru, 29.3%, (3) There is a significant contribution between foot-eye coordination with the ability to dribble in the game of soccer at the students of MTs Negeri 1 Kotabaru, by 27.2%, (4) there is a significant contribution jointly between speed, agility and eye-foot coordination with dribbling ability in a soccer game at students of MTs Negeri 1 Kotabaru, F: 12.766 and sig (p) = 0,000.Â Keyword: contribution the speed and the ability, eye-foot coordination